Data Analytics Platforms for Research in Finance - Anjali Bhute (AG Volumes, 2024)
Research techniques play a pivotal role in any financial research study or project undertaken to explore, examine or analyze data of a specific category. Several advances can be seen in the way research methods are construed and applied to get the desired results. When it comes to analyzing the financial data, we have several software to perform the task. Recent trends in data analytics have witnessed the use of many analytics platforms for conducting financial research. The chapter has listed down the various analytics platforms that are being used or most known to the finance researchers. Few of the applications of the platform techniques are being discussed through some research studies. Also, the chapter concludes with a discussion on the challenges and expected future enhancement of such applications.